(3GdfLe GdgGOi GdSGQi Edi Md GdaGX UMjM GdHNGQis - (3LeGd GdOjf eMeO Hf YHO GdSjO GdMVjQi GdMfajs; (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf,J (B261 (3g` s ((3MdH s)
(3ChdgG (B:s
(3GdMeO ddg GdPi JLdi HESeg GdQMef ai GdbOe hGJab GdYdeGA Ydi Cf CUM GdcJH cdgG GdHNGQi GdEeGe GdMGaX ai ReGfg s
(3BNQgG (B:s
(3aCfRd Gddg JYGdi GddBjI , hdgPG JJeI JCJi Ef TGA Gdgd JYGdi ai GdZRhGJ Je GdLRA GdeHGQc ef TQM GdUMjM ddHNGQi s
(3GdfSNI HgG MhGTs
(3HChdgG agQSJ ddehVhYGJ HNW eMOKs
(3Ydi ghGeTgG JUMjMGJ hJbjjOGJs
(3cJHJ GdYfGhjjf HGdMeQI s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
Keywords: (3GdMOjK h GdeUWdMs